State Healthcare Regulations and Total Knee Arthroplasty Prices Across the United States - Kevin A. Wu, BS; Katherine M. Kutzer, BS; Christian A. Pean, MD, MS; Thorsten M. Seyler, MD, PhD (Arthroplasty Today)
Background: The cost of healthcare services in the United States is subject to various regulatory influences, yet the impact of state-level healthcare policies and political affiliations on total knee arthroplasty (TKA) prices remains underexplored. Methods: Using data from the Turquoise Health Database and publicly available sources, TKA prices were analyzed across states to examine the influence of Medicaid expansion, Certificate of Need (CON) laws, and state partisan lean. Multivariable regression models controlled for Gross Domestic Product per capita, Area Deprivation Index, and urbanization. Results: Among 64,402 TKAs from 2455 hospitals ($18,164 median, interquartile range: $10,806), states with Medicaid expansion and CON laws demonstrated lower TKA prices. Republican-leaning states had significantly reduced TKA prices compared to Democrat-leaning states, even after adjusting for economic factors (P < .0001). Conclusions: Medicaid expansion and CON laws were associated with lower TKA prices across the United States. Additionally, states with Republican political leanings tended to have lower listed prices for TKA compared to Democrat-leaning states. These findings underscore the substantial influence of state healthcare policies and political factors on healthcare costs, highlighting the complexities of pricing dynamics in the US healthcare system. Level of evidence: IV